Analisis Waktu Standar untuk Menentukan Jumlah Tenaga Kerja dalam Memenuhi Permintaan Produksi Kerupuk Puli di UD. XYZ - Wibawa, Fauzan Nasik Abdullah; Satoto, Handy Febri (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
UD. XYZ in Sidoarjo encountered difficulties in meeting market demand due to an uneven imbalance of workers production stations, leading to process delays and reduced efficiency. This research aims to establish the standard time and determine the optimal workforce allocation to enhance the cracker (kerupuk puli) production process. Stopwatch time study and workload analysis were used to assess data collected through direct observation, interviews, and documentation. The findings revealed a total standard time of 1464.55 seconds or approximately 24.41 minutes to produce one 5 kg package of crackers. Based on the analysis, workforce adjustments were required: mixing and grinding increased from 1 to 2 workers, boiling decreased from 3 to 2, cooling and cutting each remained at 1, while drying and packaging were reduced from 4 to 2 workers. These changes are expected to improve efficiency and ensure production targets are consistently met.